FILANTROPI ISLAM SEBAGAI PEMBERDAYAAN EKONOMI PEMBANGUNAN (Model Pemberdayaan ZISWAF untuk 100 Usaha di Kabupaten Pamekasan) (IAIN Tulungagung, 2023)
ABSTRAK This study aims to determine the potential of philanthropic funds in economic development empowerment, as well as the distribution mechanism for 100 businesses in Pamekasan Regency in realizing the people's economy to a better level. Islamic philanthropy which consists of Zakat, Infaq, Sadaqah, and Waqf is the obligation of the people to contribute in the form of material to those who are entitled to receive it on the basis of divine values. However, the benefits of this philanthropic fund are still not optimal in improving the economy. It is proven that the distributed funds have not been managed for productive (business) activities. The method in this research is conceptual research using secondary data obtained from literature and documentaries that have been processed through a qualitative descriptive approach. The results showed that the mechanism for empowering philanthropic funds in the development economy for 100 businesses in Pamekasan Regency, by providing capital or financing as well as entrepreneurship education (entrepreneurship) with models in the form of mentoring, coaching, and training by the cooperative office. This empowerment projection has the potential to achieve the benefit of the people of the world and the hereafter. The conclusion obtained shows that philanthropy empowerment can escalate economic development, encourage regional-scale growth for 100 businesses in Pamekasan Regency.